Evaluation of the content of YouTubeTM videos about local anesthesia in pediatric dentistry - Merve Erkmen Almaz; Kamile Nur Tozar (Selcuk Dental Journal)
Abstract Aim: The purpose of this study was to assay the quality and substance of videos on YouTubeTM about local anesthesia in children and to assay whether they are practical for patients and parents. Materials and Methods: A research was applied on YoutubeTM using the search term "local anesthesia in pediatric dentistry" with the assumed sorting set to "sort by relevance". In our study, 113 videos out of 213 were excluded and 100 videos were analyzed. For video content classification, a 23-point score scale was used to classify video groups as low, moderate, and high video context. Results: Most of the videos were uploaded by healthcare professionals (n=93; 93%), while the rest were uploaded by healthcare companies/websites (n=1; 1%) and others (tv channels, news agencies) (n=6; 6%). The average duration of videos was 9.49 minutes (range: 0.5-57.57 minutes; median: 4.25). Conclusion: Although there are many videos on local anesthesia in children on YouTubeTM, these videos contain limited information in terms of content. There is a requirement to develop the quality of YouTubeTM videos on this subject by dentists.